2021
DOI: 10.51847/gsyjdovkmv
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Compounds - A Promising Leads for Antiviral Therapy

Abstract: Medicinal plants consist of a wide range of phytochemicals, which are usually described as secondary metabolites. The production of secondary metabolites in medicinal plants affects different factors, like stress and defensive responses. Various factors, such as species differences, environmental variables, and so on, will influence the type and level of the presence of secondary metabolites. Phytochemicals are produced by these medicinal plants and have a range of biological effects on human health. Polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
0
5
0
1
Order By: Relevance
“…In addition, polyphenols are non-toxic to human and animal cells. [44][45][46] Many alkaloids also exhibit highly specic antiviral activity. 47 For example, lycorine, an alkaloid isolated from Narcissus pseudonarcissus, has been shown to have antiviral properties in vitro and can protect AG6 mice from Zika virus-induced death by reducing the viral load in the mice's blood.…”
Section: Zno-extract Nanoformulationmentioning
confidence: 99%
“…In addition, polyphenols are non-toxic to human and animal cells. [44][45][46] Many alkaloids also exhibit highly specic antiviral activity. 47 For example, lycorine, an alkaloid isolated from Narcissus pseudonarcissus, has been shown to have antiviral properties in vitro and can protect AG6 mice from Zika virus-induced death by reducing the viral load in the mice's blood.…”
Section: Zno-extract Nanoformulationmentioning
confidence: 99%
“…), and aqueous solubility (mg/mL), including extracted amounts from different natural sources (Table 2). Lakadong turmeric [133,194,195 ] 194.18 780 Hydroxylcinnamic acid 0.5-3 mg/g Bamboo shoot, pineapple, bananas, spinach, and beetroot [179] Naringenin and other viruses varies with its concentration [177,178].…”
Section: Ferulic Acidmentioning
confidence: 99%
“…Lakadong turmeric [133,194,195 ] 272.25 0.47 Flavanone ~52.03 mg/g Grapefruits [164,180] Baicalein human immunodeficiency virus (HIV), influenza, etc. Daidzein's efficacy against these and other viruses varies with its concentration [177,178].…”
Section: Ferulic Acidmentioning
confidence: 99%
“…Among the many research groups investigating the viral inhibitory effect of phenolic compounds, Loaiza-Cano et al, Xu et al, Besednova et al, Ono et al, Badshah et al, and Nagarajan researched the anti-viral properties of more than 100 selected phenolic compounds, and concluded that phenolic compounds with a high number of (-OH) groups and certain specific positions obtained the highest inhibitory effect. Many of the compounds with virus-inhibitory effects were found in plants known as traditional medicinal plants or foods [ 69 , 70 , 71 , 72 , 73 , 74 ]. Chen et al reviewed the bioavailability of phenolic compounds and found that free phenolic compounds, e.g., quercetin, are presumed to partly degrade through dehydration reactions to hydroxybenzoic acids through gastric absorption, as the environment of the gastrointestinal tract possesses high bacterial conjugative enzyme activity [ 75 ].…”
Section: Introductionmentioning
confidence: 99%